Successful phytoremediation of simulated steel rolling industry heavy metals-contaminated soils using a Sorghum bicolor cultivar from Riko, Katsina, Nigeria - Yunusa, Yahaya Riko; Umar, Zubairu Darma; Kabir, Kamaluddeen (Spektrum Industri, 2024)
The release of hazardous heavy metals (HMs) from industries and other sources threatens ecosystems in Katsina, Nigeria and beyond. Bioengineering through microbially-assisted phytoremediation (MAP) is the best innovative alternative to these industries for remediating HMs contaminated environments. Sorghum bicolor (L. Moench) had been reported to be efficient in heavy metals phytoremediation. This study evaluated the ability of a fast-growing local cultivar of S. bicolor (rirrik’a/rirritsa/mota in Hausa) from Riko village, Jibiya L.G.A., Katsina State, Nigeria to remediate mesocosms simulating mixed HMs contamination obtainable at the soils of the defunct DANA Steel Rolling Mills, Katsina industrial site, to residual concentrations matching USEPA/EU limits. A chronosequential, nutrient-poor phytoremediation approach was employed to study the restoration of the contaminated soils in greenhouse experiments. The bioremoval of HMs in individual (0.05-10 g/L Cr, 0.04-1 g/L Cu, 0.08-1 g/L Pb and 0.02-1 g/L Zn) and mixed mesocosms was studied over 8 weeks, in multiple replicates, with positive and negative controls. ANOVA, Mann-Whitney and Kruskal-Wallis (with Dunn’s post-hoc) tests were used to statistically analyse the obtained data. The results confirmed an overall bioremoval of 66.67% of the HMs. Bioremoval rates were statistically similar across all HMs (one-way ANOVA: p = 0.64); with 69.48% of Zn, 67.46% of Cu, 63.34% of Cr and 58.33% of Pb bioremoved. The final residual HMs were within limits set by EPA/EU (Mann Whitney U test: p = 0.23). Study verified the status of the local cultivar of S. bicolor as a suitable agent for safe, effective phytoremediation of industrial heavy metal contaminated sites. Thus, its use is recommended for on-the-field phytoremediation of hotspots of HM contamination within the study area and beyond. The study also contributes towards sustainable and eco-friendly practices by using phytoremediation to manage environmental wastes from industrial pollution.